(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Building a good customer and brand relationship is very important, that’s why firms use an online brand community. So, the main focus of this study was to understand the antecedent and consequences of customer participation in the online brand community, concerning to loyalty behaviour through U & G Theory. The current study concentrated on social media-based different gratification which influences customer participation after that the actual behaviour of customers towards the brand was analysed. In the end mediation effect of community commitment was also checked. In this study, survey methods were used and data was collected from 202 individuals. The empirical data analysis was conducted by SEM. The findings of the study depicted that out of all gratification, only incentive plays a crucial role in customer participation and community commitment plays a considerable role in creating loyalty behaviour after that mediation effect also showed positive results.